(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
This work investigates the gender differences in complimenting strategies in a corpus of 840 Italian compliments subdivided into different sub-corpora. This study summarizes the gender-based differences in complimenting behaviour sketched by the literature, and then it explores the correlation of gender with age and topics. To this purpose, there have been analyzed the compliment responses in two sub-corpora. KEYWORDS: pragmatics, Italian, complimenting strategies, gender, linguistic behaviour